2007
DOI: 10.1188/07.onf.1218-1221
|View full text |Cite
|
Sign up to set email alerts
|

Determining Female Physicians' and Nurses' Practices and Attitudes Toward Breast Self-Examination in Istanbul, Turkey

Abstract: Female physicians and nurses need to improve their knowledge and sensitivity concerning breast cancer and BSE if they are to improve and maintain their own well-being as well as carry out their professional roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 7 publications
3
22
1
3
Order By: Relevance
“…Other studies have reported similar reasons for not applying BSE, consistent with these findings: negligence, laziness, fear of finding something related to breast cancer and anxiety, not experiencing complaints associated with breast, forgetting, lack of time, lack of information on research findings, not convinced about or not believing in the importance of BSE, finding BSE unnecessary and not knowing how to perform BSE (13,17,19,25,31,33). Performing BSE for the early diagnosis of breast cancer does not increase survival rate (34).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Other studies have reported similar reasons for not applying BSE, consistent with these findings: negligence, laziness, fear of finding something related to breast cancer and anxiety, not experiencing complaints associated with breast, forgetting, lack of time, lack of information on research findings, not convinced about or not believing in the importance of BSE, finding BSE unnecessary and not knowing how to perform BSE (13,17,19,25,31,33). Performing BSE for the early diagnosis of breast cancer does not increase survival rate (34).…”
Section: Discussionsupporting
confidence: 66%
“…Mammography ratio among nurses varies between 7.3-50.2%, and the rate found in this study was lower than previous reports from both our country and abroad (10,13,17,24,26). The reasons for not having a mammography was listed as not thinking mammography was necessary (85.4%), as not being in the mammography age group (26%) and as thinking mammography is a painful method (14.6%).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In a Norwegian study Rosvold et al, have reported that only 25.6% female workers performed monthly BSE (Rosvold et al, 2001). In two Turkish study by Canbulat et al, and Cavdar et al, of female physicians and nurses reported that 21.9% and 25% of those studied performed regular BSE, respectively (Cavdar et al, 2007;Canbulat and Uzun, 2008). An increase in perceived susceptibility has been linked to an increase in breast cancer screening (Champion et al, 1999).…”
Section: Discussionmentioning
confidence: 99%